Interface Formation and Electrical Transport in SnO2:Eu3+/GaAs Heterojunction Deposited by Sol-Gel Dip-Coating and Resistive Evaporation - Pineiz, Tatiane F. [UNESP]; Scalvi, Luis Vicente de Andrade [UNESP]; Saeki, Margarida Juri [UNESP]; de Morais, Evandro A. (Springer, 2010)
The natural n-type conduction of tin dioxide (SnO2) may be compensated by trivalent rare-earth doping. In this work, SnO2 thin films doped with Eu3+ have been deposited by the sol-gel dip-coating (SGDC) process, topped by a GaAs layer deposited by the resistive evaporation technique. The goal is the combination of a very efficient rare-earth emitting matrix with a high-mobility semiconductor. The x-ray diffraction pattern of SnO2:Eu/GaAs heterojunctions showed simultaneously the crystallographic plane characteristics of GaAs as well as cassiterite SnO2 structure. The electric resistance of the heterojunction device is much lower than the resistance of the SnO2:2 at.%Eu and GaAs films considered separately. Micrographs obtained by scanning electron microscopy (SEM) of the cross-section showed that the interface is clearly identified, exhibiting good adherence and uniformity. A possible explanation for the low resistivity of the SnO2:2 at.%Eu/GaAs heterojunction is the formation of small channels with two-dimensional electron gas (2DEG) behavior.
Keywords: Tin dioxide; gallium arsenide; heterojunction; europium